Lesión del nervio ciático : aproximación médico legal (2011)
ABSTRACT: This paper reports the expert review conducted at the Center for Law and Health Study (CENDES) on sciatic nerve injury. Analysis of findings showed that 57.1% of the causes of the sciatic —nerve injury with involvement in all cases of common peroneal nerve, superficial peroneal branch mainly his— were derived from the provision of a health service. In the evaluation of patients showed that the damage found is not only structural but also involves the aesthetic, functional, psychological and social alter, overall, the state bio-psycho-social and economic individual. It may involve legal implications for the health care provider.